First record of Lasiurus arequipae in the Department of Tacna, Perú - Mamani-Contreras, Ruth; Aragón-Alvarado, Giovanni (Therya Notes, 2021)
Lasiurus arequipae was recently described in the Department of Arequipa as a new species endemic to Perú, and its geographic distribution is poorly known. The presence of this species is reported in Lomas de Sama Grande, Department of Tacna, Perú. The specimen was collected during a study on the local fauna of bats, identified with the taxonomic key of Málaga et al. (2020), and compared with the holotype and paratypes deposited in the Scientific Collection of the Museum of Natural History at Universidad Nacional de San Agustín, Arequipa, Perú. The specimen is an adult female, preserved as skin, skull, and skeleton (not cleaned). One map of the current distribution of L. arequipae and information on the ecology of the species are included. We observed a potential shelter associated with the olive tree. This new record is located 287 km southwest of the town of Huatiapa, which is the closest record site where the first study took place in the Department of Arequipa. This finding brings to 11 the number of species of bats for the Department of Tacna. We recommend further sampling using supplementary methods to expand our knowledge of the natural history and ecology of this species and set conservation actions.